1996
DOI: 10.4319/lo.1996.41.4.0755
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic study of variations in the fluorescence based maximum quantum efficiency of photosynthesis across the North Atlantic Ocean

Abstract: Using ship-based phytoplankton fluorescence techniques on a 9-d transect of the North Atlantic Ocean, we have produced the first synoptic view of variations in the maximum quantum yield of photosynthetic energy conversion (4,) on an ocean-wide basis. Based on our 4, measurements, the North Atlantic can be divided into two basins. The southeastern basin (from the African coast to the midocean ridge) is characterized by relatively little horizontal variation in 4, over vast stretches of the ocean. In the northwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
2
18
1
3
Order By: Relevance
“…Nanomolar increases in nitrate concentration have been shown to support high surface productivity in Sargasso Sea waters (Glover et al, 1988), and an inverse correlation between integrated productivity and the depth of the nutricline has been previously reported in several nutrient-poor regions of the Atlantic Ocean (Herbland and Voituriez, 1979;Malone et al, 1993). The notion of the phytoplankton growth rate being nitrogen limited in vast areas of the Atlantic Ocean agrees with the observed geographical distribution of the maximum quantum e$ciency of photosynthesis (Geider et al, 1993;Olaizola et al, 1996) and the results of nutrient addition experiments in the North Atlantic . Finally, the correlation between the abundance of N -"xing cyanobacteria and growth rate found between the Equator and 203N during suggests that biological "xation of atmospheric nitrogen can also be an important mechanism in sustaining high biological rates in nutrient-impoverished surface waters (see Karl et al, 1997).…”
Section: Phytoplankton Growth In the Oligotrophic Regionssupporting
confidence: 73%
See 2 more Smart Citations
“…Nanomolar increases in nitrate concentration have been shown to support high surface productivity in Sargasso Sea waters (Glover et al, 1988), and an inverse correlation between integrated productivity and the depth of the nutricline has been previously reported in several nutrient-poor regions of the Atlantic Ocean (Herbland and Voituriez, 1979;Malone et al, 1993). The notion of the phytoplankton growth rate being nitrogen limited in vast areas of the Atlantic Ocean agrees with the observed geographical distribution of the maximum quantum e$ciency of photosynthesis (Geider et al, 1993;Olaizola et al, 1996) and the results of nutrient addition experiments in the North Atlantic . Finally, the correlation between the abundance of N -"xing cyanobacteria and growth rate found between the Equator and 203N during suggests that biological "xation of atmospheric nitrogen can also be an important mechanism in sustaining high biological rates in nutrient-impoverished surface waters (see Karl et al, 1997).…”
Section: Phytoplankton Growth In the Oligotrophic Regionssupporting
confidence: 73%
“…Nevertheless, despite the great diversity of physical processes operating over large spatial scales (e.g. Olaizola et al, 1996), we still found a signi"cant relationship between phytoplankton growth and the physical and chemical structure of the water column. Similarly, we have shown in a companion study that the light-saturated, chlorophyll a-normalized photosynthetic rate was inversely correlated to the depth of the nutricline (MaranoH n and Holligan, 1999).…”
Section: Phytoplankton Growth In the Oligotrophic Regionsmentioning
confidence: 88%
See 1 more Smart Citation
“…7-8). The Fv/Fm ratio, which was driven by phytoplankton community structure as well as nutrient stress (Olaizola et al, 1996;Suggett et al, 2009), showed higher values in the High treatment at stations PM7 and S412 compared with the controls (Fig. 7).…”
Section: Physiological Charactersmentioning
confidence: 99%
“…For example, room-temperature fluorescence induction is a powerful in vivo indicator of contaminant-related damage to photosystem quantum efficiency in higher plants (Krupa et al 1993;Prevot et al 1993;Streb et al 1993;Sgardelis et al 1994;Gensemer et al 1996;Huang et al 1997a). While Chl a fluorescence induction assays have been used widely in terrestrial plant stress physiology (Hipkins and Baker 1986;Krause and Weis 1991) and in studies examining patterns of marine algal photosynthesis (Falkowski et al 1991;Greene et al 1992;Hofstraat et al 1994;Olson and Zettler 1995;Olaizola et al 1996;Olson et al 1996), its use in freshwater plant contaminant studies is still in its infancy. Furthermore, low-temperature (77ЊK) chlorophyll fluorescence emission scans can present qualitative information regarding the structure and organization of photosystem reaction center pigments (Hipkins and Baker 1986;McCormac et al 1996;Marwood and Greenberg 1996).…”
mentioning
confidence: 99%